Ganglion Cell Topography Indicates Pre- or Postnatal Damage to the Retro-Geniculate Visual System, Predicts Visual Field Function and May Identify Cerebral Visual Impairment in Children – A Multiple Case Study. (2nd November 2019) - Jacobson, Lena; Lennartsson, Finn; Nilsson, Maria
ABSTRACT: In this paper, we quantify the degree of ganglion cell layer thinning due to retrograde trans-synaptic degeneration (RTSD) from retro-geniculate damage in six cases who had homonymous visual field defects known since childhood. Three had prenatal injuries, occurring close to mid-gestation and in the first parts of the early and late third trimester, respectively, and representing injuries at different early developmental stages. Three had later acquired injuries, at age 1.5, 4 and 13 years. The impact of the injury to the optic radiations was revealed by fibre tractography. The ganglion cell thinning corresponded with the visual field defects and the extent and location of the primary brain damage. The most important sign of RTSD was asymmetry of the ganglion cell topography within the macular area.